Physical Metallurgy and Thermodynamics of Aluminum Alloys Containing Cerium and Lanthanum - Hosseinifar, Mehdi (My University, 2009)
The development of highly formable aluminum alloy sheets is of great interest to the automotive industry, because they provide a lightweight alternative to steel sheet for structural panels. Finding ways to improve the formability of Al alloys is the main subject of the present investigation. This issue is tackled from two angles. First, a possibility of fabricating a two-phase material containing newly discovered ductile intermetallic compounds is considered. The Al-La-Mg system is thermodynamically optimized accompanied with a differential thermal analysis (DTA) experiment to validate the optimization results. A new approach is introduced to deal with the incompatibility of phase models in binary Al-La and La-Mg systems. This approach is successfully applied to the Laves and B2 phases in the binary La-Mg system. A utilization of the thermodynamic description of the Al-La-Mg system to model solidification at low and high cooling rates shows that it is impossible to fabricate such a two-phase material by casting.
Second, the effect of small additions of cerium and lanthanum on Fe-bearing intermetallics in a wrought heat-treatable Al alloy is examined. Fe-containing intermetallics are known to deteriorate the formability of Al alloys by acting as void nucleation sites. It is found that in alloys containing 0.1-0.2 wt. % of lanthanum, the fraction of less harmful Chinese script particles is pronouncedly higher than that in the reference alloy. In addition to this advantage, much smaller grains are seen in the alloy with 0.2 wt. % La. Despite similarities between La and Ce, the latter metal neither modifies the microstructure nor noticeably affects the gram size. Hot rolling and solutionizing nullifies the beneficial effect of small La additions resulting in no improvement in the formability of the alloy.
In order to understand how lanthanum affects the phase portrait of the alloy, a socalled direct thermal analysis experiment is performed. Solidification paths are derived for slowly cooled alloys by coupling the results of this investigation with microstructural observations. The likelihood of two modification mechanisms is speculated using these solidification paths.
Novel Aluminum Alloys Containing Cerium and Lanthanum
Keywords: material science and engineering, aluminum, alloy, cerium, lanthanum